2017
DOI: 10.1016/j.lungcan.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of FGFR3-TACC3 fusions as a potential by-pass resistance mechanism to EGFR tyrosine kinase inhibitors in EGFR mutated NSCLC patients

Abstract: Resistance to EGFR tyrosine kinase inhibitors (TKIs) in non-small cell lung cancers (NSCLCs) with activating EGFR mutations generally involve development of acquired secondary or tertiary EGFR mutations, such as T790M or C797S. However, case reports have demonstrated that actionable receptor tyrosine kinase fusions such as EML4-ALK, CCDC6-RET, and FGFR3-TACC3 can potentially confer resistance to EGFR TKIs. We seeked to identify the prevalence of FGFR3-TACC3 fusion transcripts as resistance mechanism to EGFR TK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 15 publications
2
28
1
Order By: Relevance
“…Notably, in the Indian cohort FGFR3-mutated ADCs occurred in younger patients and concomitantly harbored EGFR-mutations in 25% of cases [9], as in our patient. Moreover, activating oncogenic fusions between FGFR3 intron 17/exon 18 and TACC3 can occur in lung ADC and function as bypass-mechanism associated with intrinsic/acquired resistance to EGFR-TKIs reversible by FGFR-inhibitors [10][11][12]. Collectively, these observations raise the possibility that FGFR3 D785fs*31 may represent a mechanism of intrinsic resistance to EGFR-TKIs that could partially explain the rapid progression during this treatment and could be targetable by FGFR-inhibitors.…”
Section: Discussionmentioning
confidence: 97%
“…Notably, in the Indian cohort FGFR3-mutated ADCs occurred in younger patients and concomitantly harbored EGFR-mutations in 25% of cases [9], as in our patient. Moreover, activating oncogenic fusions between FGFR3 intron 17/exon 18 and TACC3 can occur in lung ADC and function as bypass-mechanism associated with intrinsic/acquired resistance to EGFR-TKIs reversible by FGFR-inhibitors [10][11][12]. Collectively, these observations raise the possibility that FGFR3 D785fs*31 may represent a mechanism of intrinsic resistance to EGFR-TKIs that could partially explain the rapid progression during this treatment and could be targetable by FGFR-inhibitors.…”
Section: Discussionmentioning
confidence: 97%
“…22 FGFR3-TACC3 fusions were also identified as acquired bypass resistance mechanisms to all generations of EGFR tyrosine kinase inhibitors. 4,24 In MET-driven NSCLC, MET Y1230C was detected in the ctDNA of a patient with a known MET exon 14 skipping mutation following treatment with crizotinib, and another report showed EGFR amplification as a likely resistance mechanism to crizotinib in a case of MET-amplified NSCLC. 25,26 These clinical cases highlight the utility of ctDNA testing, particularly to detect diverse mechanisms of acquired resistance and avoid rebiopsy after progression during targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The National Comprehensive Cancer Network (NCCN) guidelines for NSCLC now recommend broad molecular profiling, including testing for alterations in 7 genes (EGFR, ALK receptor tyrosine kinase gene [ALK], ROS1, BRAF, MNNG HOS Transforming gene [MET], erb-b2 receptor tyrosine kinase 2 gene [ERBB2], and ret protooncogene gene [RET]) to inform selection of effective targeted therapies, many of which are now approved for the treatment of advanced NSCLC, as well as testing for KRAS mutations. 1 Furthermore, diverse alterations predicting sensitivity and resistance to targeted therapies continue to be elucidated, [2][3][4] making comprehensive assessment throughout the course of disease progression critical for optimal patient care.…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic hybrid capture-based genome profiling of formalin-fixed paraffin-embedded tissue samples and circulating tumor DNA samples from 17 319 lung cancer patients found five cases of FGFR3-TACC3 fusion. 108 Mechanistic investigation suggested that fusion of FGFR3-TACC3 functions as a bypass resistance mechanism to pretreated EGFR-TKIs, such as naquotinib, afatinib, erlotinib, and osimertinib in these lung cancer patients. 108 A 49-year-old…”
Section: Fibroblast Growth Factor Receptor Signalingmentioning
confidence: 99%